Characterization of mutants of human immunodeficiency virus type 1 that have escaped neutralization by a monoclonal antibody to the gp120 V2 loop. - Yoshiyama, H (1994)
The biologically cloned human immunodeficiency virus type 1 (HIV-1) RF isolate is sensitive to neutralization by the murine monoclonal antibody (MAb) G3-4 to a conformationally sensitive epitope in the V2 loop of HIV-1 gp120. To assess how variation in the V2 amino acid sequence affects neutralization by this MAb, we cultured RF in the presence of G3-4 to select neutralization escape mutants. Three such mutants resistant to G3-4 neutralization were generated from three independent experiments. Solubilized gp120 from each of these escape mutants had a reduced affinity for G3-4 and also for two other V2 MAbs that were able to bind the wild-type RF gp120. PCR sequencing of the entire gp120 of the wild-type RF virus and the escape mutants showed that amino acid substitutions had occurred only at two positions, Y177H and L179P, both in V2. Experimental introduction of the Y177H substitution into the RF V2 loop in the context of the NL4-3 molecular clone re-created the G3-4-resistant phenotype. The L179P mutant was not viable. Thus, our findings confirm that the HIV-1 V2 loop contains the conformationally sensitive neutralization epitope recognized by G3-4 and that a single amino acid substitution within this region can result in escape variants that arise from immune selection pressure.